1998
DOI: 10.4269/ajtmh.1998.59.769
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of soluble egg antigen in urine of Schistosoma haematobium-infected children from Kenya.

Abstract: Abstract. While research on alternative diagnostic and morbidity markers for infection with Schistosoma haematobium has been going on for a long time, egg counts continue to be used as the gold standard, and infection intensity is thought to reflect the severity of the disease. However, this relationship is not always clear and fluctuation in egg output makes it difficult to classify prevalence correctly. The use of circulating adult worm antigen detection as an alternative diagnostic technique has been applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…We have previously described an assay detecting SEA in the urine of S. haematobium-infected individuals and have found significant correlations with egg counts, hematuria, and ultrasound-detectable pathology. 9,13 In the current study, similar correlations were also observed both before therapy with praziquantel and 18 months after therapy. Clearance of SEA from the urine was slower compared with egg counts and levels increased significantly six months after treatment, about two months later than egg counts; SEA levels continued to increase in parallel with egg counts and overall pathology.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We have previously described an assay detecting SEA in the urine of S. haematobium-infected individuals and have found significant correlations with egg counts, hematuria, and ultrasound-detectable pathology. 9,13 In the current study, similar correlations were also observed both before therapy with praziquantel and 18 months after therapy. Clearance of SEA from the urine was slower compared with egg counts and levels increased significantly six months after treatment, about two months later than egg counts; SEA levels continued to increase in parallel with egg counts and overall pathology.…”
Section: Discussionsupporting
confidence: 85%
“…10 Two schools were selected for the study, Tsunguni with an initial prevalence of 86% and Kibaokiche with a prevalence of 77%. From the group previously described, 9 117 children participated in all follow-up examinations: 52 from Tsunguni and 65 from Kibaokiche of whom 59 were boys and 58 were girls (age range ϭ 6-15 years, median ϭ 9 years).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate sample collection for immunodiagnosis, urine samples have been used to test for schistosomiasis, [8][9][10][11] malaria, 12 leishmaniasis, 13 Chagas disease, 14 and filariasis. [15][16][17] In human filariasis, the usefulness of immunoglobulin (Ig) G4 in the diagnosis of filarial infections has been reported.…”
Section: Introductionmentioning
confidence: 99%